The association between industry specialist auditor and financial reporting timeliness- post MFRS Period - Ahmad, Maslina; Mohamed, Hamidah; Puat Nelson, Sherliza (2016)
This study examines audit report lag as one of the mechanisms to measure timeliness of financial reporting. The convergence of International Financial Reporting Standards (IFRS) with Malaysian Financial Reporting Standards (MFRS) might challenge the auditors to issue their listed clients’ audited financial statements on time. The presence of industry specialist auditors is believed to be able to reduce the audit report lag and subsequently enhance financial reporting timeliness. The overall results of the study suggest that the appointment of industry specialist auditors to undertake auditing work under full MFRS convergence improves financial reporting timeliness.